How big should the pilot study for my cluster randomised trial be?. (June 2016) - Eldridge, Sandra M; Costelloe, Ceire E; Kahan, Brennan C; Lancaster, Gillian A; Kerry, Sally M
There is currently a lot of interest in pilot studies conducted in preparation for randomised controlled trials. This paper focuses on sample size requirements for external pilot studies for cluster randomised trials. We consider how large an external pilot study needs to be to assess key parameters for input to the main trial sample size calculation when the primary outcome is continuous, and to estimate rates, for example recruitment rates, with reasonable precision. We used simulation to provide the distribution of the expected number of clusters for the main trial under different assumptions about the natural cluster size, intra-cluster correlation, eventual cluster size in the main trial, and various decisions made at the piloting stage. We chose intra-cluster correlation values and pilot study size to reflect those commonly reported in the literature. Our results show that estimates of sample size required for the main trial are likely to be biased downwards and very imprecise unless the pilot study includes large numbers of clusters and individual participants. We conclude that pilot studies will usually be too small to estimate parameters required for estimating a sample size for a main cluster randomised trial (e.g. the intra-cluster correlation coefficient) with sufficient precision and too small to provide reliable estimates of rates for process measures such as recruitment or follow-up rates.